Stretchable Sensors for Nanomolar Glucose Detection. Issue 4 (17th February 2020) - Imamura, Amanda; Zakashansky, Julia; Cho, Kenny; Lin, Lancy; Carrilho, Emanuel; Khine, Michelle
Abstract: Biosensors that detect analytes in sweat face the challenge of maintaining sensitivity upon miniaturization. Various materials and processes have been developed to create nanostructured electrodes with high surface areas to mitigate this issue. The need remains, however, for biocompatible materials that can be scalably integrated into wearable devices. This paper details a gold thin‐film electrode fabricated using a thermoplastic shape memory polymer to create hierarchical wrinkled structures via the miniaturization process, followed by transfer onto a soft, stretchable substrate. The final stretchable electrode, which is ≈30 times smaller than that of the original, unshrunk electrode, retains its original surface area. Even more remarkably, further enhancement in current density is achieved upon stretching the electrode to 210% of its original length; improved sensitivity remains stable after relaxation of the polymer. Stretching aids diffusion limited reactions, such as the reduction and oxidation of [Fe(CN)6 ] 3−/4− . The stretchable electrodes sensitively detect glucose without enzymes or additional labels at physiological pH in the range of 1 × 10 −7 –1 × 10 −4 m with a calculated limit of detection of 2.22 × 10 −8 m, among the lowest reported for a flexible, enzyme‐free sensor. Abstract : Leveraging shape memory polymers to create wrinkled electrodes, this soft sensor is ≈30 times smaller yet retains its original surface area. Further enhancement in current density is achieved upon stretching; improved sensitivity remains stable after relaxation of the polymer to allow enzyme‐free detection of glucose at physiological pH with a limit of detection of 2.22 × 10 −8 m .